Estudio de las relaciones entre especies del género Capsicum cultivadas en Colombia a partir de HPLC-MS y análisis estadístico multivariado (2020)
In the present work an extensive bibliographic revision was made, as well as the preparation of diverse fruit samples of the genus Capsicum cultivated in Colombia. The previous work allowed to establish a procedure for the future characterization of the samples and their classification using high performance liquid chromatography coupled with mass spectrometry (HPLC-MS) and multivariate statistical analysis.